Total knee arthroplasty in extra articular deformities: A series of 36 knees - Rajgopal, Ashok (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: The presence of extra articular deformities either in the femur or the tibia with arthritis of the knee makes total knee arthroplasty (TKA) technically demanding. The purpose of this study is to report outcomes with Total Knee Arthroplasty in patients with arthritis of the knee associated with extra articular deformity by intraarticular resection and soft tissue balancing. MATERIALS AND METHODS: Thirty six knees (32 patients) who had arthritis of the knee associated with extra articular deformity, underwent total knee arthroplasty between 1999 and 2006 were included in this retrospective analysis. All patients had intraarticular resection with soft tissue balancing to correct the deformity. Full length weight bearing anteroposterior X-rays, Knee society scores, and Knee range of motion was recorded pre- and postoperatively. RESULTS: The mean period of followup was 85 months (range 42-120 months). The deformities amenable to correction by intraarticular resection in our series were Femur- Coronal plane 11°-18° (mean 16.2°) Saggital plane 0°-15° (mean 10.1°) Tibia - Coronal plane 12°-24° (mean 21°). There was an improvement in the range of motion from mean of 54° preoperatively to 114° postoperatively (P value < 0.05). The Knee Society- Knee Score improved from 37 points to 85 points postoperatively (P value < 0.05). The functional score improved from a mean value of 19 to a mean of 69.5 at followup (P < 0.01). The preoperative hip knee ankle angle in the coronal plane improved from a mean of 14° ± 2° varus (26° varus to 4° valgus) to a mean of 2° ± 0.6° varus (6° varus to 2° valgus). CONCLUSION: With a good preoperative planning and templating, intraarticular bone resection and good soft tissue balancing both in flexion and extension, correction would be possible in majority of extraarticular deformities.